LITERATURE REVIEW : Hubungan Durasi Lama Duduk Terhadap Endurance Pada Lansia - Khairunisa (2020)
Objective: Sitting is an activity thats people usually do. Especially the elderly who do a lot of daily activities while sitting. This study aims to analyze the associations between duration of sitting and endurance in elderly, this literature review is analyzed through journals and articles that have been found. Method: study literature is the method that used in this literature review with searching and also arrage the results about some study that have done before systematically from literature, journals, articles, research results in several databases such as Google Scholar, Science Direct, Elsevier, PEDRO, PubMed by using certain keywords in the period 2011-2020. From the literature search results, it was found 5 articles and journals that met the source inclusion criteria. The methodological quality assessment of 5 journals was assessed with the Scimago Journal & Country Rank (SJR). Results : The results obtained Analysis was carried out on 5 journals in accordance with the discussion conducted by the author. Results: The results obtained from the literature review which is supported by 5 journals is found that there was a decrease in elderly endurance. Conclusion : there is significant decrease with endurance in elderly who so sitting in a long duration.